Micro-Defects-Related Low Cycle Fatigue Mechanical Model of the Nuclear-Grade S30408 Stainless Steel - Huiping Liu; Mingkun Xiao; Jiannan Hao; Xinjie Ma; Ni Jiang; Qing Peng; Chao Ye (Nanomaterials)
Continuous and interrupted low cycle fatigue tests were conducted on nuclear-grade S30408 stainless steel under different stress conditions at room temperature. Vickers hardness testing and microstructure characterization were performed on the fatigue samples with different fatigue states. The evolutionary mechanism of the microstructure defects in materials under fatigue cyclic loading was discussed. The traditional Basquin formula was used to predict the fatigue life of these fatigue samples. At the same time, a quantitative mechanical model related to the characteristic micro-defects parameter KAM and the Vickers hardness (Hv) was established for the S30408 stainless steel during the low cycle fatigue damage process, and the prediction accuracy of the Vickers hardness is greater than 90%, which is significant and useful for the fatigue life prediction of the 304 stainless steels used in nuclear systems and the safe operation of the reactors.